Konsep Pengembangan Destinasi Pariwisata Terpadu Pada Objek Wisata Pulau Kumala, Kabupaten Kutai Kartanegara - Tambunan, Ribka Elizabeth; Nugroho , Rizky Arif; Dewanti, Ajeng Nugrahaning; Putra, Rulliannor Syah (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Kumala Island is one of the leading tourist destinations in Kutai Kartanegara Regency. During the COVID-19 pandemic, this tourism attraction was closed, causing the condition of Kumala Island to become unmaintained and reduce the attractiveness of tourist visits. Therefore, an integrated tourism area development concept is needed at Kumala Island tourist destination. The data collection method used was a primary survey and the analysis used was the scoring method to evaluate the existing conditions of Kumala Island tourism objects based on the 6A components (attractions, amenities, accessibility, accommodation, activities and ancillary), the delphi analysis method to determine the factors that influence integrated tourism development, and qualitative descriptive analysis with the triangulation method to produce an integrated tourism development concept formulation. The research results are in the form of an integrated tourism development concept formulation on Kumala Island Tourism Objects, among others, creating integrated information facilities, integrating emergency medical services and easily accessible health services, creating safe and comfortable public areas, improving the quality of sanitation facilities, developing recreational facility infrastructure, and forming public-private partnerships. Keywords : writing concept, tourism, development, integrated, tourist